Self‐Sensing Robotic Structures from Architectured Particle Assemblies - Xudong Yang; Zongzheng Wang; Bojian Zhang; Tianyu Chen; Changhong Linghu; Kunlin Wu; Guohui Wang; Hailu Wang; Yifan Wang (Advanced Intelligent Systems, 2023)
The tight coupling of shape transformation, stiffness tuning, and self‐sensing that biological organisms exhibit has long served as inspiration for next‐generation soft robots. However, most current soft robots rely on intrinsically soft materials for actuation, separately embedded sensors for sensing, and have fixed stiffness once fabricated. Large gaps remain between these soft robots and biological organisms where multifunctionality is realized within an integrated body. Herein, a new class of robotic structures from architectured particle assemblies is introduced. They combine three functions: shape changing, stiffness variation, and self‐sensing into one monolithic structure. Unlike traditional entirely soft robots, the design utilizes the geometric contacts of stiff, architectured particles under confining pressure to achieve these functions. The applications of these structures by designing smart self‐sensing architectures and soft grippers are demonstrated. The design provides a new paradigm of multifunctional robotic structures, with potential multiscale applications in adaptive robots, smart devices, and reconfigurable architectures.